Rancang Bangun Media Pertumbuhan Karang Dengan Menggunakan Metode Bioreeftek - Kismanto Koroy; Iswandi Wahab; Safyan Popa (Jurnal Sumberdaya Akuatik Indopasifik, 2021)
Coral reefs are one of the invertebrates that inhabit an ecosystem, and there is various aquatic biota. Coral reef ecosystems have an essential role both ecologically for aquatic biota and physically as a barrier to sea waves leading to coastal areas. Artificial reef media (bioreeftek) is a new technology in developing of transplantation methods using natural materials such as coconut shell waste and bamboo. The research objective is about the resistance level of the design of coral growth media (bioreeftek). This research was conducted from August to October 2020 by designing the coral reef bioreeftek media, starting with studying the bioreeftek media design method, collecting tools and materials, to making and placing the media in a predetermined location. Making bioreeftek media as many as eight media, with 81 bamboo poles (9 poles for one medium) and 243 coconut shells were prepared. From the observations' results when placing and the first observation to the second observation with the integrity of 100%, which indicates a reasonably efficient media construction.